Aetiology of livestock fetal mortality in Mazandaran province, Iran - Amouei, Afsaneh; Sharif, Mehdi; Sarvi, Shahabeddin; Bagheri Nejad, Ramin; Aghayan, Sargis A.; Hashemi-Soteh, Mohammad Bagher; Mizani, Azadeh; Hosseini, Seyed Abdollah; Gholami, Sara; Sadeghi, Alireza; Sarafrazi, Mohammad; Daryani, Ahmad (PeerJ, 2019)
In the farming industry, the productivity of livestock herds depends on the fertility efficiency of animals. The accurate diagnosis of a broad range of aetiological agents causing fetal death is often difficult. Our aim was to assess the prevalence rates of Toxoplasma gondii, Neospora caninum, and Brucella spp. infections in ruminant abortion using bacteriological culture and molecular techniques in Mazandaran Province, northern Iran. Samples were collected from 70 aborted sheep, goat, and cattle fetuses between September 2014 and December 2015. Necropsy was performed on all the received samples, and brain tissue and abomasal content were obtained from the aborted fetuses. Protozoan infections were detected by specific polymerase chain reaction (PCR) and bacterial agents using bacteriological examinations and PCR assay. Infectious pathogens were detected in 22 out of 70 (31.4%) examined fetuses. Moreover, T. gondii, N. caninum, and B. melitensis were verified in 13 (18.6%), four (5.7%), and two (2.85%) samples, respectively. Our results showed that infection with the mentioned pathogenic agents may lead to fetal mortality, which can be a major cause of economic loss. The listed pathogens could be considered important etiological agents of fetal loss in Mazandaran Province, for which appropriate control measures such as vaccination and biosecurity can be implemented to prevent infection and reduce reproductive loss in livestock farms.
Keywords: Aetiology; Livestock; Fetal mortality; Iran